Leading the Change with Six Images of a Change Leader - Mojibola Bamidele-Sadiq (Westcliff University, 2018)
Change is constant, and it is a continuous norm. It has even been said that, "to refuse to change is to be left behind" (anonymous). While difficult, this is still something that both individuals and organizations must cope with. The world is constantly changing, which explains why individuals and organizations that are open to change continue to survive. Many researchers have argued that an organization may only achieve a successful change when there is effective leadership. Effective leaders are those who understand when to change and how much to change. The purpose of this paper is to reiterate the importance of leadership in implementing a successful and transformational change in an organization. It will further explore a body of literature that supports and identifies roles leaders take on in the change management process.